Nursing process in neonate with delay in the surgical recovery for duodenal atresia - Sánchez-Juárez, Itzel Andrea (Universidad de Sonora, 2021)
Introduction: Duodenal atresia is a congenital malformation where a functional or anatomic abnormality causes normal intestinal motility’s disorders. The definitive treatment includes a surgical repair, whose main goal is to recover the intestinal continuity. Neonates treated with this kind of procedures have a high morbidity associated to surgical complications, sepsis, and dehiscence of surgical wound. Objective: Implement the nursing process by using the NANDA, NOC, NIC, and GPC taxonomies in order to contribute to the management of the newborn with delayed surgical recovery from duodenal atresia. Methodology: It was addressed through a case study in which the stages of the nursing process were implemented; the assessment was done by patterns functional health of Marjory Gordon, the altered patterns were prioritized and diagnosis labels were identified. Case presentation: 22-day old neonate extrauterine, was born from 38.5 SDG in a public hospital, post operated on intestinal plasty; the neonate had a dehiscent and infected surgical wound. The neonate showed signs of acute pain and gastrointestinal motility complications such as bloating and gastric residue. Auxiliary diagnosis results showed thrombocytopenia and increased C reactive protein. Conclusion: The hierarchical organization of the affected functional patterns allowed executing a care plan and taking care of the needs of the neonate, all of that through interventions sustained on scientific evidence.